Synchrotron FTIR Microspectroscopy of Single Natural Silk Fibers - Ling, Shengjie; Qi, Zeming; Knight, David P; Shao, Zhengzhong; Chen, Xin (Biomacromolecules, 2011)
Synchrotron FTIR (S-FTIR) microspectroscopy was used to monitor the silk protein conformation in a range of single natural silk fibers (domestic and wild silkworm and spider dragline silk). With the selection of suitable aperture size, we obtained high-resolution S-FTIR spectra capable of semiquantitative analysis of protein secondary structures. For the first time, we have determined from S-FTIR the β-sheet content in a range of natural single silk fibers, 28 ± 4, 23 ± 2, and 17 ± 4% in Bombyx mori, Antheraea pernyi, and Nephila edulis silks, respectively. The trend of β-sheet content in different silk fibers from the current study accords quite well with published data determined by XRD, Raman, and 13C NMR. Our results indicate that the S-FTIR microspectroscopy method has considerable potential for the study of single natural silk fibers.